ASSOCIATED SYMPTOMATHOLOGY WITH SEXUAL OFFENDERS IN PRISON. - Castro, María-Esther; López-Castedo, Antonio; Sueiro, Encarnación (Anales de Psicología / Annals of Psychology, 2009)
In this investigation a study of the symptoms of psychological malaise of 20 internal punished men of the Prison of Pereiro de Aguiar (Ourense) who fulfilled sentence by crimes against the sexual freedom, with an age rank that oscillated between the 22 and 61 years old. Two sub-groups in function of the type of crime committed with object formed to compare their psychopathological profiles: those that fulfilled sentence by sexual crimes against adult victims and the suffered ones by sexual crimes against minors. To all the internal ones it was applied to the Clinical Interview and the Registry to them, the Listing of Symptoms (SCL-90-R), the State-Trait Anger Expression Inventory (STAXI), the Scale of Impul-sividad (BIS-II) and the Scale of Self-esteem, obtaining the sociodemo-graphical, penal and psychopathological profile in which, besides to find the global scores of the group of sexual delinquents in general, the scores of sub-group were compared both. The results indicate that the sexual delinquents of adult women present/display more symptoms of hostility, whereas in the child abusers more symptoms of phobic anxiety with a significant level of gravity are detected.